Climate change adaptation: a corrective policy framework in the Malaysian agricultural sector - Akhtar, Rulia; Masud, Muhammad Mehedi; Noman, Abu Hanifa Md; Jabin, Nazneen; Alam, A.S.A. Ferdous (Inderscience, 2019)
A corrective policy framework is essential for sustainable agricultural management. In order to put in place a corrective policy framework, it is necessary to know the socio-economic context of local farmers and their perception of climate change. Therefore, the main objective of this study is to explore their socio-economic status and general perception of climate change and to examine its impact on adaptation practices. To achieve the research objectives, data were collected using survey questionnaires and analysed using statistical tools. The results show that most of the respondents are between the age of 31-45 years in the sample size, 45% has secondary education and 34% of the respondents' monthly income is between RM2,000-RM4,000. It has been found that approximately 76% of farmers had heard about climate change. The results also revealed that socio-economic characteristics such as education, income, type of farmer, attitudes and awareness were positive and highly significant. It is hoped that the findings of this study would be useful for policymakers in designing an appropriate policy framework to raise awareness of how to reduce the impact of climate change in the agricultural sector. Copyright © 2019 Inderscience Enterprises Ltd.